Arctic sustainability research: toward a new agenda. (2nd July 2016) - Petrov, Andrey N.; BurnSilver, Shauna; Chapin, F. Stuart; Fondahl, Gail; Graybill, Jessica; Keil, Kathrin; Nilsson, Annika E.; Riedlsperger, Rudolf; Schweitzer, Peter
ABSTRACT: The Arctic is among the world's regions most affected by ongoing and increasing cultural, socio-economic, environmental and climatic changes. Over the last two decades, scholars, policymakers, extractive industries, local, regional and national governments, intergovernmental forums, and non-governmental organizations have turned their attention to the Arctic, its peoples and resources, and to challenges and benefits of impending transformations. The International Conference on Arctic Research Planning (ICARP) has now transpired three times, most recently in April 2015 with ICARP III. Arctic sustainability is an issue of increasing concern within the Arctic and beyond it, including in ICARP endeavors. This paper reports some of the key findings of a white paper prepared by an international and interdisciplinary team as part of the ICARP-III process, with support from the International Arctic Science Committee Social and Human Sciences Working Group, the International Arctic Social Sciences Association and the Arctic-FROST research coordination network. Input was solicited through sharing the initial draft with a broader network of researchers, including discussion and feedback at several academic and community venues. This paper presents a progress report on Arctic sustainability research, identifies related knowledge gaps and provides recommendations for prioritizing research for the next decade.